2017
DOI: 10.1111/psyp.12868
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exercise posture on executive function in transient ischemic attack patients

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 42 publications
(48 reference statements)
0
31
1
Order By: Relevance
“…There is no known data with which to establish a clinically meaningful change in prefrontal cortex tHb. However, CALF resulted in a 2.5 μM decrease in prefrontal cortex tHb, compared to the ~23 μM increase we previously reported, with the same NIRS device, during 30 min of moderate intensity cycling exercise (Faulkner et al, ).…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…There is no known data with which to establish a clinically meaningful change in prefrontal cortex tHb. However, CALF resulted in a 2.5 μM decrease in prefrontal cortex tHb, compared to the ~23 μM increase we previously reported, with the same NIRS device, during 30 min of moderate intensity cycling exercise (Faulkner et al, ).…”
Section: Discussioncontrasting
confidence: 60%
“…Additionally, the lack of change in estimated executive function over time may reflect the lack of sensitivity in the Stroop task with this population. We elected to use the Stroop task because it is relatively short, which would minimize mental stimulation during sitting, and it is a classic measure of prefrontal cortex function (MacLeod, ) that has been widely used to assess the effects of acute exercise on cognition (Faulkner et al, , ; Lambrick et al, ). Nonetheless, the young healthy participants in the current study may not have found the Stroop tasks sufficiently challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations